Securing Virtual Images in Cloud Environment - Shiv Kumar Tiwari, Subhrendu G. Neogi, Ashish Mishra (Mathematical Statistician and Engineering Applications, 2023)
The new technology can offer on demand resources remotely with the help of new emerging expertise called cloud computing. Cloud computing helps users to work in an environment where physical infrastructure is not required at user end. There are many protocols which helps to access the resources provided by the cloud computing. Cloud computing is Internet based technology, which is charged on the basis of usage, demand and is offered to users of resources and services on them. The exact location where the user is to be configured is hidden from all cloud servers.. In the proposed work, user-generated secure key is used for authentication and at the time of virtual machine (VM) switching. Every time when a user requests for a new service from another VM, it has to authenticate. To authenticate genuine user, a secure pass key is used every time, it ensures security and authentication between system and user.